Clarification of taxonomic status of Pseudochorthippus geminus (Mistshenko, 1951) (Orthoptera: Acrididae: Gomphocerinae) based on male calling song analysis - Tishechkin, Dmitri Yu. (Zootaxa, 2024)
Pseudochorthippus geminus is redescribed and illustrated based on specimens from southern Kazakhstan and northern Kyrgyzstan. Oscillograms of the male calling songs of P. geminus from these localities and of P. parallelus from southern Kazakhstan are given. Comparative analysis of the song temporal patterns of P. geminus and P. parallelus clearly indicates that they represent separate biological species, but the morphological differences between them are indistinct and do not always provide reliable characters for species diagnostics.